Pengaruh Penggunaan Aplikasi MyEarTraining terhadap Kemampuan Kepekaan Nada dan Kemampuan Bernyanyi Siswa - Fawzi, Mochamad Ikbal (Jurnal Pena Ilmiah, 2019)
One of the problems in learning music in elementary school is the lack of singing skills of students. Not all students can sing well and correctly. One of the causes of this problem is the lack of sensitivity to tone. In fact, tone sensitivity is one of the basic skills that music must possess. In this study, the solution offered to overcome this problem is to use the MyEarTraining application in learning music. This study used a quasi-experimental method. The subject of this study consisted of 32 students in the experimental class and 30 students in the control class. Based on the research that has been done, learning to use the MyEarTraining application causes changes in tone sensitivity and student singing abilities. This study also explained the relationship between tone sensitivity and students' singing abilities.